The effect of particle acidity on secondary organic aerosol formation from alpha-pinene photooxidation under atmospherically relevant conditions - Han, Yuemei; Stroud, Craig A.; Liggio, John; Li, Shao-Meng (ATMOSPHERIC CHEMISTRY AND PHYSICS, 2016)
Secondary organic aerosol (SOA) formation from photooxidation of alpha-pinene has been investigated in a photochemical reaction chamber under varied inorganic seed particle acidity levels at moderate relative humidity. The effect of particle acidity on SOA yield and chemical composition was examined under high-and low-NOx conditions. The SOA yield (4.2-7.6 %) increased nearly linearly with the increase in particle acidity under high-NOx conditions. In contrast, the SOA yield (28.6-36.3 %) was substantially higher under low-NOx conditions, but its dependency on particle acidity was insignificant. A relatively strong increase in SOA yield (up to 220 %) was observed in the first hour of alpha-pinene photooxidation under high-NOx conditions, suggesting that SOA formation was more effective for early alpha-pinene oxidation products in the presence of fresh acidic particles. The SOA yield decreased gradually with the increase in organic mass in the initial stage (approximately 0-1 h) under high-NOx conditions, which is likely due to the inaccessibility to the acidity over time with the coating of alpha-pinene SOA, assuming a slow particle-phase diffusion of organic molecules into the inorganic seeds. The formation of later-generation SOA was enhanced by particle acidity even under low-NOx conditions when introducing acidic seed particles after alpha-pinene photooxidation, suggesting a different acidity effect exists for alpha-pinene SOA derived from later oxidation stages. This effect could be important in the atmosphere under conditions where alpha-pinene oxidation products in the gas-phase originating in forested areas (with low NOx and SOx) are transported to regions abundant in acidic aerosols such as power plant plumes or urban regions. The fraction of oxygen-containing organic fragments (CxHyO1+ 33-35% and CxHyO2+ 16-17 %) in the total organics and the O / C ratio (0.52-0.56) of alpha-pinene SOA were lower under high-NOx conditions than those under low-NOx conditions (39-40, 17-19, and 0.61-0.64 %), suggesting that alpha-pinene SOA was less oxygenated in the studied high-NOx conditions. The fraction of nitrogen-containing organic fragments (CxHyNz+ and CxHyOzNp+) the total organics was enhanced with the increases in particle acidity under high-NOx conditions, indicating that organic nitrates may be formed heterogeneously through a mechanism catalyzed by particle acidity or that acidic conditions facilitate the partitioning of gas-phase organic nitrates into particle phase. The results of this study suggest that inorganic acidity has a significant role to play in determining various organic aerosol chemical properties such as mass yields, oxidation state, and organic nitrate content. The acidity effect being further dependent on the timescale of SOA formation is also an important parameter in the modeling of SOA.